From Citizen's Rights to Civic Responsibilities - Lucas Ronconi (Institute of Labor Economics (IZA), 2019)
In less developed countries the state does not extends its legality homogenously. A share of the population suffers its absence or its illegal presence. In this article we argue that such irregular state intervention has more negative consequences that previously thought. Individuals who suffer lack of access to citizen's rights blame the state for their hardship, and negatively reciprocate by ignoring their civic duties. The building blocks of our hypothesis are attribution theory and reciprocity. We provide evidence based on self-report survey data for almost one hundred developing countries; an observational study where compliance with civic duties can be objectively assessed; and a list experiment. The evidence indicates that people who are discriminated by government officials, or workers who do not receive legally-mandated benefits, are less likely to comply with civic duties such as voting and paying taxes. Exclusion erodes civic responsibilities.
Keywords: H26; I38; D63; 330; reciprocity; trust; taxes; voting; rights; citizenship